2007
DOI: 10.2152/jmi.54.331
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of syndecan isoforms during mouse incisor amelogenesis

Abstract: : Syndecans are transmembranous heparan sulfate proteoglycans (HSPGs) with covalently attached glycosaminoglycan side-chains located on the cell surface. The mammalian syndecan family is composed of four types of syndecans (syndecan-1 to -4). Syndecans interact with the intracellular cytoskeleton through the cytoplasmic domains of their core proteins and membrane proteins, extracellular enzymes, growth factors, and matrix components, through their heparan-sulfate chains, to regulate developmental processes.Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Syndecan-1 seems to play several important roles including fine-tuning of various growth factors' activity (Mali et al 1993;Su et al 2007) and consequential maintenance of co-ordinated growth in developing tissues (Vainio and Thesleff 1992), modulation of epithelial-mesenchymal interactions (Vainio et al 1989), as well as proliferation and differentiation (Hall and Miyake 1995). Reports from extensive research on syndecan-1 during tooth development on experimental animals (Bai et al 1994;David et al 1993;Muto et al 2007;Salmivirta et al 1991) and recombinant tissues (Vainio et al 1989;Vainio and Thesleff 1992) are additionally confirmed by the present study. Generally, expression of syndecan-1 during cap and bell stages of human odontogenesis showed constant increase in mesenchymal parts of the tooth germ, followed by the steady decrease in epithelial parts (enamel organ), thus displaying a complete epithelial-to-mesenchymal shift by the late cap stage.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Syndecan-1 seems to play several important roles including fine-tuning of various growth factors' activity (Mali et al 1993;Su et al 2007) and consequential maintenance of co-ordinated growth in developing tissues (Vainio and Thesleff 1992), modulation of epithelial-mesenchymal interactions (Vainio et al 1989), as well as proliferation and differentiation (Hall and Miyake 1995). Reports from extensive research on syndecan-1 during tooth development on experimental animals (Bai et al 1994;David et al 1993;Muto et al 2007;Salmivirta et al 1991) and recombinant tissues (Vainio et al 1989;Vainio and Thesleff 1992) are additionally confirmed by the present study. Generally, expression of syndecan-1 during cap and bell stages of human odontogenesis showed constant increase in mesenchymal parts of the tooth germ, followed by the steady decrease in epithelial parts (enamel organ), thus displaying a complete epithelial-to-mesenchymal shift by the late cap stage.…”
Section: Discussionsupporting
confidence: 85%
“…These studies imply complementary roles of syndecans during odontogenesis as has been shown for other proteoglycans of extracellular matrix (Hou et al 2012). Syndecan-1 is predominantly expressed in proliferating parts of tooth germ in a stage-specific manner tightly regulated by epithelial-mesenchymal interactions Vainio and Thesleff 1992), and seems to take part in the plethora of processes involved in tooth development spanning from cell condensation and growth control Vainio and Thesleff 1992) in the earliest stages, through amelogenesis and dentinogenesis (Muto et al 2007) in the advanced stages of tooth development. In Msx1 mutant, syndecan-1 was specifically reduced in dental mesenchyme, causing failure of tooth morphogenesis such as arrest of molar tooth development (Maas et al 1996).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Syndecans family constitutes the most abundant HSPGs expressed on the surface of mammalian cells [21], [22], [23]. Four members in the syndecan family have been described in the mammalian cells (syndecan-1 to 4).…”
Section: Introductionmentioning
confidence: 99%
“…HS commonly occurs as part of proteoglycans, where HS GAG chains are attached to a core protein via a trisaccharide linkage on a serine residue forming the HSPG [75]. The syndecan family is one of the most abundant HSPGs expressed on mammalian cells [76][77][78]. There are four members in the syndecan family (syndecan-1, 2, 3 and 4) composed of a single membrane-spanning domain, a conserved transmembrane domain, and an extracellular domain that is specific for each syndecan ( [79].…”
Section: Heparan Sulfate Proteoglycans (Hspgs)mentioning
confidence: 99%